Impacts of green infrastructures on aerodynamic flow and air quality in Porto's urban area. (October 2018) - Rafael, S.; Vicente, B.; Rodrigues, V.; Miranda, A.I.; Borrego, C.; Lopes, M.
Abstract: Air pollution is an environmental and social issue at different spatial scales, especially in a climate change context, with an expected decrease of air quality. Despite the technological evolution of the last decades in the transport sector, road traffic emissions are still one major source of air pollution at the city level. The main goal of this study was to evaluate the influence of a set of resilience measures, based on nature-based solutions, in the wind flow and in the dispersion of air pollutants, in a built-up area in Portugal. For that, two pollutants were analysed (NOX and PM10) and four scenarios were developed: i) a baseline scenario, ii) an urban green scenario, iii) a green roof scenario, and iv) a "grey" scenario (without trees). Two models were used, namely the Weather Research and Forecasting model (WRF) and the CFD model VADIS (pollutant dispersion in the atmosphere under variable wind conditions). The WRF model was used to initialize the CFD model, while the last was one used to perform the set of numerical simulations, on hourly basis. The implementation of a green urban area promoted a reduction of air pollutants concentrations, of about 16% [PM10] and 19% [NOx] in the overall domain; while the application of green roofs showed an increase of concentrations (reaching 60% during specific time periods). Overall the results showed that a strategic placement of vegetation in cities has the potential to make an important contribution to the improvement of air quality and sustainability of urban environments. Highlights: Cities must become resilient to be able to deal with increase air pollution. A high detail CFD model coupled with a vegetative canopy model was used. Resilience scenarios were studied by assessing its influence on PM10 and NOX levels. Green areas improve cities air quality, by increasing air pollutants dispersion. Local air quality can be optimised based on knowledge-based planning of green areas.